The use of modern mathematics teaching methods for the first three grades in Al-Shubak Brigade schools from the perspective of teachers in Jordan - Al-Shalabi, Najwa Mohammed (Journal of Educational and Psychological Sciences, 2020)
This study aimed to reveal the role of modern teaching methods in teaching mathematics for the first three grades in Shobak brigade schools from the point of view of teachers in Jordan. The researcher used the descriptive-analytical method, where a research tool was designed consisting of three areas: Randomly selected, there were 55 male teachers and 74 female teachers. One of the most important results of the study is: The overall tool got an overall average (4.36 out of 5), and at the field level, the field of preparation for teaching got the highest average (4.70), then the field of learning methods with an average (4.16) and finally; The field of learning patterns averages (4.21), all of them rated (high), as shown that there are no statistically significant differences between the average grades of teachers and teachers in modern teaching methods of mathematics attributed (sex, educational qualification, and years of experience), while it was found that there are statistically significant differences between the average grades of teachers and teachers of modern teaching methods of material Mathematics according to the sex variable was in favor of males in the first and third areas, and the second area was in favor of females, the researcher made the following recommendations: The necessity of diversity in teaching methods, taking into account the interests of students and their inclinations and acquiring research and investigation skills, and the need to train students to use the means of information technology efficiently so that they can follow the rapid and growing development in science, the development of curricula in line with modernity and contemporary requirements.